2008
DOI: 10.1007/s00239-008-9162-9
|View full text |Cite
|
Sign up to set email alerts
|

Do Amino Acid Biosynthetic Costs Constrain Protein Evolution in Saccharomyces cerevisiae?

Abstract: Prokaryotic organisms preferentially utilize less energetically costly amino acids in highly expressed genes. Studies have shown that the proteome of Saccharomyces cerevisiae also exhibits this behavior, but only in broad terms. This study examines the question of metabolic efficiency as a proteome-shaping force at a finer scale, examining whether trends consistent with cost minimization as an evolutionary force are present independent of protein function and amino acid physicochemical property, and consistent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
59
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 28 publications
6
59
1
Order By: Relevance
“…Moreover, unicellular organisms may have a relatively lower ability to complete for limited resources. Previous studies have indicated that unicellular microbes tended to undergo economical evolution at the level of an entire protein or even an entire proteome by, for example, preferentially using less biosynthetically expensive amino acids in their highly expressed proteins and extracellular proteins to counteract the potential loss of cellular resources [34,42-45]. Our analyses have shown that, compared with Eukaryota, the Archaea and Bacteria proteomes contain more of the inexpensive amino acids like Ala, Gly, Ile, and Val, and fewer of the expensive residues like Gln, His, and Trp (Figure 1) [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, unicellular organisms may have a relatively lower ability to complete for limited resources. Previous studies have indicated that unicellular microbes tended to undergo economical evolution at the level of an entire protein or even an entire proteome by, for example, preferentially using less biosynthetically expensive amino acids in their highly expressed proteins and extracellular proteins to counteract the potential loss of cellular resources [34,42-45]. Our analyses have shown that, compared with Eukaryota, the Archaea and Bacteria proteomes contain more of the inexpensive amino acids like Ala, Gly, Ile, and Val, and fewer of the expensive residues like Gln, His, and Trp (Figure 1) [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…According to several measures, Trp emerges as the most energetically costly of the amino acids (46), and recent studies with S. cerevisiae have substantiated this (47). If amino acid import is inhibited, the magnitude of the metabolic burden experienced by the cell should reflect the relative biosynthetic cost of de novo synthesis of the affected amino acid(s).…”
Section: Discussionmentioning
confidence: 99%
“…This presumably reflects some essential aspect of protein structure or folding. However, Met is less abundant than the other hydrophobic residues [71], and is less likely to accommodate a structural requirement [72]. Furthermore, biosynthesis of Met is more energetically expensive than other members of the hydrophobic group [69,71,73].…”
Section: Discussionmentioning
confidence: 99%